Shutdown and recovery of the AMOC in a coupled global climate model: The role of the advective feedback. Issue 6 (27th March 2013) - Jackson, L. C.
<x xml:space="preserve">Abstract</x> [1] The fresh water advection into the Atlantic ocean by the overturning circulation (Fov) has been suggested as an indicator of the stability of the Atlantic Meridional Overturning Circulation (AMOC) through an advective feedback. This feedback is explored in transient simulations with a global climate model with and without flux adjustments. Flux adjustments are shown to alter the model near surface salinity, changing Fov from a net importer, to a net exporter of fresh water, mainly through correcting an Atlantic saline bias. The AMOC recovers in strength from a collapsed state, however, that in the experiment with flux adjustments recovers much later and more slowly than that without flux adjustments. This difference is traced back to the sign of Fov, confirming the indicator's importance for the AMOC and suggesting that model biases affecting Fov need to be addressed in order to assess the likelihood of irreversible changes in the AMOC.